Bridging the Gaps between Teacher Educators and Student Teachers’ Perceptions about the Attributes of Effective Teacher Educators - Karim, Sayit Abdul (Register Journal, 2021)
The present study attempts to investigate effective EFL teacher educators from the perspectives of student teachers and teacher educators. A survey design was employed to examine student teachers' and teacher educators' perceptions of the attributes of effective EFL teacher educators. Furthermore, an adapted questionnaire was administered online to 408 participants (334 student teachers, and 74 teacher educators) to obtain data about effective EFL teacher educators using four categories of attributes of effective teacher educators, namely subject matter knowledge (SMK), pedagogical knowledge (PK), organization and communication skills (OCS), and socio-affective skills (SAS). Descriptive statistical analyses were conducted for the measurement of central tendency. The findings revealed the student teachers and teacher educators have different perceptions of how they perceived effective EFL teacher educators. There was a significant statistical difference between student teachers and teacher educators' perceptions of the three categories of attributes, namely SMK, PK, and OCS. Meanwhile, there was no significant statistical difference between student teachers and teacher educators' perceptions of SAS. The results of the present study may serve several pedagogical implications in the program of teacher education context.Keywords: EFL student teachers, teacher Educators, effective teacher, perceptions